Pneumococcal infection among hospitalized Egyptian children. Issue 2 (June 2015) - Draz, Iman H.; Halawa, Eman F.; Wahby, Ghada; Ismail, Dalia K.; Meligy, Bassant S.
<x xml:space="preserve">Abstract</x> Aim We aimed to describe the detection rate spectrum of clinical manifestations, and outcome of pneumococcal disease in children younger than 5 years admitted to the largest referral pediatric hospital in Egypt. Materials and methods This was a hospital-based study to detect laboratory-confirmed Streptococcus pneumoniae cases among children younger than 5 years. Data on demographic characteristics, clinical diagnosis, comorbidities, diagnostic tests, antibiotic resistance, and clinical outcome were collected during the study years from 2008 to 2011. Results During the 4-year study period, 22 018 cases younger than 5 years had cultures performed at Cairo University Pediatric Hospital microbiology laboratory. We estimated the annual detection rate of total Streptococcus pneumonia infection to be 54.5/100 000. The incidence of invasive pneumococcal disease (IPD) was half the incidence of non-IPD (18.2 and 36.4/100 000, respectively). Infants of 1 year or younger were statistically more vulnerable to Streptococcus pneumonia infection compared with children between 1 and 5 years of age (annual rate: 110.5/100 000 and 21.6/100 000, respectively). The overall pneumococcal annual case fatality was 33.3% and was higher in IPD (75%) than in non-IPD (12.5%) cases. There was an obviously increasing trend of the pneumococcal detection rate throughout the 4 years of the study (P<0.0001). Conclusion and recommendations Our results confirm the substantial and increasing pneumococcal infection, the emerging of multidrug resistant isolates, and the vulnerability of the younger age group and high-risk population, which calls for a national surveillance to inform policy and decision-making before national wide vaccine introduction.